Remineralization of dentine tubules induced by phosphate-terminated PAMAM dendrimers. Issue 12 (December 2020) - Wen, Yajie; Wang, Jichao; Luo, Jun; Yang, Jiaojiao
Abstract: Various sealants have been developed to treat the exposure of dentinal tubules (DTs) and further dental hypersensitivity. Herein, the phosphate-terminated fourth generation polyamidoamine dendrimers (PAMAM-PO3 H2 ) was successfully synthesized. Six duplicates of demineralized dentin and type I collagen matrix were incubated in artificial saliva solution with or without PAMAM-PO3 H2 treatment at 37 °C for 2 weeks, respectively. The artificial saliva solution was replaced every day. These regenerated crystals on the surface of dentin and collagen matrix were confirmed to be hydroxyapatite (HAp). The approach thus demonstrates that PAMAM-PO3 H2 can offer an efficient therapy for seal DTs in clinical dentistry. Abstract : biomimetic mineralization, PAMAM dendrimers, dentine tubules sealants, collagen, hydroxyapatite